"You Don't Know Who This Man Is": Hospitality and Trauma in Alexandra Wood's The Human Ear - ERDURUCAN, BÜŞRA (Walter de Gruyter, 2021)
This paper explores the themes of hospitality and trauma in Alexandra Wood's The Human Ear (2015) by focusing on the modes of encounter with the Other in the play. As Lucy, a woman in her twenties, tries to come to terms with the death of her mother as a result of an unspecified bomb attack, she finds out that her estranged brother, Jason, killed himself. In the meantime, however, a man who claims to be her brother keeps turning up at her door, and through these encounters we can trace the possibilities and limits of hospitality. By referring to the theories of Emmanuel Levinas, Jacques Derrida, and Sara Ahmed on home and hospitality, this paper argues that in The Human Ear, the redefinition of the relationship with the Other is represented as a means to come to terms with trauma as Lucy's process of welcoming the stranger is connected to her process of healing from trauma.
Keywords: Alexandra Wood; The Human Ear; Emmanuel Levinas; Jacques Derrida; Sara Ahmed